Transcriptional profiling during foetal skeletal muscle development of Piau and Yorkshire–Landrace cross-bred pigs - Sollero, B. P.; Guimarães, S. E. F.; Rilington, V. D.; Tempelman, R. J.; Raney, N. E.; Steibel, J. P.; Guimarães, J. D.; Lopes, P. S.; Lopes, M. S.; Ernst, C. W. (Animal Genetics, 2011)
Skeletal muscle development is a complex process involving the coordinated expression of thousands of genes. The aim of this study was to identify differentially expressed genes in longissimus dorsi (LD) muscle of pigs at 40 and 70 days (d) of gestation (developmental stages encompassing primary and secondary fibre formation) in Yorkshire–Landrace (YL) cross-bred pigs and Piau pigs (a naturalized Brazilian breed), which are two breed types that differ in muscularity. Foetuses were obtained from gilts at each gestational age (n = 3 YL; n = 4 Piau), and transcriptional profiling was performed using the Pigoligoarray microarray containing 20 400 oligonucleotides. A total of 486 oligonucleotides were differentially expressed (fold change (FC) ‡ 1.5; false discovery rate (FDR) £ 0.05) between 40 and 70 d gestation in either YL or Piau pigs, and a total of 1300 oligonucleotides were differentially expressed (FC ‡ 1.5; FDR £ 0.05) between YL and Piau pigs at either age. Gene ontology annotation and pathway analyses determined functional classifications for differentially expressed genes and revealed breed type–specific developmental expression patterns. Thirteen genes were selected for confirmation by qRT-PCR analyses, and expression patterns for most of these genes were confirmed, providing further insight into the roles of these genes in pig muscle development. This study revealed both developmental and breed type–specific patterns of gene expression in foetal pig skeletal muscle, including genes not previously associated with myogenesis. This information will contribute to future pig genetic improvement efforts.
Keywords: Foetal skeletal muscle; Pig; Transcriptional profiling